A ductile chromium–molybdenum alloy resistant to high-temperature oxidation - Frauke Hinrichs; Georg Winkens; Lena Katharina Kramer; Gabriely Falcão; Ewa M. Hahn; Daniel Schliephake; Michael Konrad Eusterholz; Sandipan Sen; Mathias Christian Galetz; Haruyuki Inui; Alexander Kauffmann; Martin Heilmaier (Nature, 2025)
Abstract Even with the rapid development of renewable energy sources, improving the efficiency of energy conversion from fossil or synthetic fuels remains a challenge because, for example, combustion engines in long-range aircraft will still be needed in the upcoming decades1. Increasing their operating temperatures (1,050–1,150 °C (refs. 2–4)) is one option. This requires replacing single-crystalline Ni-based superalloys in the hottest sections of turbines by refractory-element-based materials, which exhibit much higher solidus temperatures beyond 2,000 °C (refs. 5–7). Here we introduce a single-phase Cr-36.1Mo-3Si (at.%) alloy that meets, for the first time, to our knowledge, the most important critical requirements for refractory-element-based materials: (1) relevant resistance against pesting, nitridation and scale spallation at elevated temperatures, minimum up to 1,100 °C, and (2) sufficient compression ductility at room temperature. Although strength and creep resistance in such alloys were already superior to Ni-based superalloys in several cases, oxidation/corrosion resistance, mandatory to withstand the combustion atmosphere, and ductility/toughness, needed for damage tolerance and device setting, still pose barriers for the development or application of refractory-element-based candidate materials. Any previous successful attempts to address the otherwise catastrophic oxidation of Mo and nitridation of Cr during oxidation suffered from a loss in ductility at ambient temperatures.